2018
DOI: 10.1038/s41598-018-29121-2
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Biofilm Dispersal on the Host

Abstract: Chronic infections are often associated with the presence of a biofilm, a community of microorganisms coexisting within a protective matrix of extracellular polymeric substance. Living within a biofilm can make resident microbes significantly more tolerant to antibiotics in comparison to planktonic, free-floating cells. Thus, agents that can degrade biofilms are being pursued for clinical applications. While biofilm degrading and dispersing agents may represent attractive adjunctive therapies for biofilm-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 31 publications
5
116
0
Order By: Relevance
“…For this, we did not measure biofilm mechanics but rather biofilm dispersal, because we have previously shown that biofilm dispersal in combination with antibiotic therapy is an effective treatment for biofilm infections. 8, 47 Dispersal happens when the bacteria in a biofilm infection convert to the planktonic state; we anticipated that compromising biofilm mechanics would promote dispersal.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this, we did not measure biofilm mechanics but rather biofilm dispersal, because we have previously shown that biofilm dispersal in combination with antibiotic therapy is an effective treatment for biofilm infections. 8, 47 Dispersal happens when the bacteria in a biofilm infection convert to the planktonic state; we anticipated that compromising biofilm mechanics would promote dispersal.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we previously found that the generic glycoside hydrolases, which have only minimal effect on biofilms grown in vitro , result in far more dispersal on biofilms grown in the same manner in vivo than do the specific enzymes. 8, 47 One explanation for this apparent discrepancy might be that the changes in biofilms associated with dispersal are not primarily mechanical in nature. Another possibility is that the matrix produced in vivo might not have the same population of polymers as that produced by the same strain in vitro , and therefore might not have appropriately specific targets for the alginate lyase and DNase I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, biofilms enhance the ability of bacteria to generate "persister" sub-populations, which are multi-drug tolerant, essentially dormant cells with a characteristic gene expression signature 24 . Dispersal of a biofilm has the potential to seed a patient with drug-resistant bacteria 25,26 . Strategies are needed to break down biofilms associated with indwelling medical devices and chronic infections, in order to render bacteria sensitive to antibiotics and susceptible to immune clearance.…”
mentioning
confidence: 99%